PERANCANGAN BUKU FOTOGRAFI EMPON-EMPON DENGAN TEKNIK ENVIRONMENTAL PORTRAIT SEBAGAI SARANA PENGENALAN KEPADA REMAJA - Hari Saputera, Rizal Amandara; Budiardjo, Hardman; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2017)
Abstract: Medicinal currently almost alienated and less attractive to teens because of the large reduction of land occurred and the emergence of a wide range of modern processed food. This happens due to lack of awareness to appreciate and preserve the original heritage of Indonesia. Medicinal include one legacy that must be preserved, therefore the purpose of this study was to design a photography book medicinal portrait with environmental engineering as a means of introduction to adolescents. Medicinal is part of the culture in Indonesia where the plant is located. In the midst of the massive land reduction and fast food that presents a wide range of selection, medicinal began to be forgotten among teenagers. From the analysis of these data, obtained keyword "essential" (something that is very important). The main concept can also be interpreted as the most prominent of the rival, through the selection of design minimalism medicinal expected to be more prominent than any other product or any other modern processed food is more popular today. Adolescent disinterest towards medicinal caused by the absence of the introduction to them. Medicinal also a cultural diversity depends on its type. Currently medicinal've lost identity or less popular among teenagers. Designing a photography for each medicinal alone is expected to attract teenagers to the local heritage, because at the age that is quite mature, they will be more interested in the things that are easy to digest, such as crop photos, food photography, environmental photos and other.Kata Kunci: Buku Fotografi, Empon-empon, Environmental, Warisan Lokal, Essential